Analisis struktur pengeluaran rumah tangga di Provinsi Jambi Tahun 2020 - Rizkiansyah, Nicky; Amir, Amri; Zulfanetti, Zulfanetti (Jurnal Paradigma Ekonomika, 2022)
The purpose of this study was to determine the effect of household groups on the structure of household expenditures. The data used in this study is the March 2020 Susenas raw data, namely Susenas data on household scores in 11 districts and cities of Jambi Province. The data analysis method used is descriptive method. The analytical tool used is Multiple Linear Regression (multiple regression). The results showed that in the upper urban household group, the independent variables were: household income, number of household members, age of the head of the household, education level of the head of the household, gender of the head of the household, the status of the head of the household in the main occupation, and the status of the household head. marriage of the head of the household can explain household non-food competition by 94.3 percent and together the independent variables can have an influence on household non-food expenditure. In the lower urban household group, the independent variables cannot explain expenditures other than household food because they only have an R2 value of 2.7 and together the independent variables also cannot have an effect on expenditures other than household food. As well as in the upper rural household group, the independent variable can explain household non-food competition by 65.5 percent and the independent variable can have an influence on household non-food expenditure.